Blended-Based Experiential Learning Model as A Strategy to Improve Entrepreneurship Skills of Social Science Education Students - Pusposari, Luthfiya Fathi; Mintarti, Sri Umi; Wahyono, Hari; Handayati, Puji; Sari, Ulfi Andrian; Prasad, Ravinesh Rohit (International Journal of Social Learning (IJSL), 2024)
Entrepreneurship represents one of the skills that universities must teach their students to prepare them for the workforce. The research objective is to investigate the effectiveness of blended-based experiential learning as a strategy for improving entrepreneurial skills. The pre-test and post-test control group design was the research model. The subject is students enrolled in entrepreneurship education courses at the Social Science Education Department Universitas Islam Negeri Malang, Indonesia. The experimental group used experiential learning, and the control group used traditional learning. Entrepreneurial skills instrument consists of 19 valid and reliable using likert scale statement items. The analysis of data using independent sample t-test. The findings revealed a significance value of 0.000<0.05, indicating that the model successfully enhances entrepreneurial skills. The implication is the model can be an effective reference in teaching entrepreneurship. Through hands-on experience, students can discover knowledge and improve entrepreneurial skills through online and offline learning (blended).